Tuning the morphology to enhance the catalytic activity of α-Ag2WO4 through V-doping - Lima Patrocinio, Katiana (2023)
Here, we present the synthesis of a highly efficient V-doped α-Ag2WO4 catalyst for the oxidation of sulfides to sulfones, exhibiting a high degree of tolerance towards various sensitive functional groups. Remarkably, the catalysts with 0.01% V-doping content exhibited outstanding selectivity towards the oxidation process. Scavenger experiments indicated the direct involvement of electron-hole (e−/h+) pairs, hydroxyl radical (˙OH), and singlet oxygen (1O2) in the catalytic mechanism. Based on the experimental and theoretical results, the higher activity of the V-doped α-Ag2WO4 samples was associated with the preferential formation of the (100) surface in the catalyst morphology.